Body fat percentage and Body Mass Index in association with menstrual irregularities in young adults: A cross-sectional study - Bryan Gervais de Liyis; George David; Made Favian Budi Gunawan (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS